1991
DOI: 10.1149/1.2085434
|View full text |Cite
|
Sign up to set email alerts
|

Chemical‐Mechanical Polishing for Fabricating Patterned W Metal Features as Chip Interconnects

Abstract: Interconnect features of W metal, recessed in an SiO2 dielectric, can be formed using a novel chemical‐mechanical polish process. Mechanical action, to continually disrupt a surface passivating film on W, and chemical action, to remove W, appear to be requirements for workability of the process. A trial process chemistry using a ferricyanide etchant is described. Removal of the W is discussed in terms of competition between an etching reaction which dissolves W and a passivation reaction to reform WO3 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
263
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(273 citation statements)
references
References 11 publications
(24 reference statements)
9
263
1
Order By: Relevance
“…Kaufman et al 17) studied the CMP of W with slurries containing silica or alumina abrasive and oxidant K3Fe(CN)6 below a pH of 6.5. They suggested that WO3 was formed on the W surface by the oxidant and that the oxide film played an important role in creating a mirror finish.…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman et al 17) studied the CMP of W with slurries containing silica or alumina abrasive and oxidant K3Fe(CN)6 below a pH of 6.5. They suggested that WO3 was formed on the W surface by the oxidant and that the oxide film played an important role in creating a mirror finish.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematically, the competitive adsorption process can be represented by two reactions, shown as Eqs. [1] and [2], that compete with each other for tungsten, W, surface sites following methods applied in gas adsorption (16). The adsorption of charged species is the expected outcome based upon traditional adsorption theory (17,18).…”
Section: Evaluation Of Competitive Adsorption Processesmentioning
confidence: 99%
“…The adsorption of charged species is the expected outcome based upon traditional adsorption theory (17,18). The reactions [1] and [2] can also be written in terms of equilibrium constants K 1 and K 2 as shown in Eqs. [3] and [4].…”
Section: Evaluation Of Competitive Adsorption Processesmentioning
confidence: 99%
“…4 In contrast, Kaufmann et al proposed a synergistic model for metal CMP that attributes material removal during CMP of metals to the cyclic removal of the passive layer on the surface of a metal through mechanical abrasion by abrasives and pad asperities, and subsequent active oxidative dissolution of the metal from the resulting exposed regions, until the passive layer has been regenerated. 9 This model implicitly assumed that the passive layer was thick enough that the underlying unoxidized metal was not removed by abrasion. Tripathi et al proposed a quantitative model similar to Kaufmann's by postulating a quasi-steady state where the overall rate of removal of passivating material and the overall rate of growth of passivating material are balanced, giving a constant overall MRR during copper CMP.…”
mentioning
confidence: 99%